The Influence of Company Growth, Retained Earnings, and Institutional Ownership on Bond Ratings (A Study on Banking Companies Rated by PT PEFINDO in 2020–2024) - Arafah, Shafa Nurul; Khairunnisa, Khairunnisa (SAFE-Network, 2026)
Bond ratings serve as indicators of a company’s ability to meet its financial obligations and as a reference for investors in assessing risk. In the banking sector, these ratings reflect a company’s stability and credibility in managing default risk. This study analyzes the effect of company growth, retained earnings, and institutional ownership on the bond ratings of banking firms rated by PT PEFINDO during the 2020–2024 period, with bond ratings classified into investment grade and non-investment grade using a dummy variable. The research employs a quantitative approach using logistic regression analysis. The sample was selected through purposive sampling, consisting of banking companies listed on the Indonesia Stock Exchange that were consistently rated by PEFINDO. The study utilizes secondary data obtained from annual financial reports and PEFINDO’s official publications. The results indicate that, partially, company growth does not have a significant effect on bond ratings. Retained earnings, however, significantly affect bond ratings as they signal financial stability and the company’s capacity to fulfill its obligations. Institutional ownership shows no significant effect, suggesting that the proportion of institutional shareholders does not directly reflect monitoring effectiveness. Simultaneously, all three independent variables significantly influence bond ratings.